Retrospective analysis of image characteristics of 76 cases of cerebral vascular fenestrations - Xu, Luyao; Chen, Xiaodi; Xiang, Wei; Wei, Hongchun; Liang, Zhigang (Frontiers in Neurology, 2022)
Objectives: To summarize the clinical and imaging features of cerebral vascular fenestration and to explore the association between cerebral vascular fenestration and cerebral infarction and aneurysm. Materials and Methods: The computed tomography angiography (CTA), magnetic resonance angiography (MRA), and digital subtraction angiography (DSA) imaging data of 76 cases of cerebral vascular fenestration from January 2021 and December 2021 in the Yantai Yuhuangding Hospital Affiliated to Qingdao University were analyzed. The general information was described. The location, morphology, and size of cerebral vascular fenestration were described. The association between cerebral vascular fenestration and infarction and aneurysm were analyzed. Results: Among 76 patients, a total of 80 fenestrations were detected (two patients had three fenestrations), and basilar artery fenestration was most common (28/80). The fenestration <5 mm were 43/80, 5–10 mm were 12/80, and ≥10 mm were 25/80. Moreover, 19 patients had other vascular diseases: 10 with aneurysms, 5 with moyamoya diseases, and 4 with cerebral artery dissections. Except for one aneurysm at the site of the fenestration, other aneurysms were separate from the fenestrations. In addition, 37 patients had cerebral infarctions, of which 16 had cerebral infarctions in the blood supply area of the arterial fenestration. Among these 16 patients, there was more cerebral infarction in posterior circulation than in anterior circulation. However, no statistically significant differences were detected in the risk factors between fenestration-relevant cerebral infarctions group and non-fenestration-relevant cerebral infarctions group. Also, fenestration was common in anterior circulation in patients <60-years-old, but no difference was detected in the age in fenestration located in posterior circulation. Conclusions: In our study, cerebral vascular fenestration occurred most frequently in basilar artery and may be combined with other vascular diseases. Fenestration in posterior circulation may be related to cerebrovascular diseases, while fenestration in anterior circulation is common in patients <60-years-old. Nonetheless, no clear clinical relevance was observed between fenestration and cerebral infarction. Also, we didn’t find a definitely association between fenestration and aneurysm. For fenestration patients with cerebral infarctions, long-term antiplatelet and statin therapy may be safe and effective.